2018
DOI: 10.4102/sajhrm.v16i0.913
|View full text |Cite
|
Sign up to set email alerts
|

Total rewards and its effects on organisational commitment in higher education institutions

Abstract: Orientation: Retaining staff with special endeavours within higher education institutions has become a top priority and crucial for any organisational productivity and competiveness. Attracting and retaining talent has remained a critical and complex issue for human capital management in organisations.Research purpose: The purpose of this study was to investigate the impact of total rewards on organisational commitment measured by Total Rewards Scale and Organisational Commitment Questionnaire.Motivation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 24 publications
4
46
1
Order By: Relevance
“…The reward system is central to the hiring and retention of employees in an organization. Obicci (as cited in Mabaso and Dlamini, 2018) observed that for any employer to be able to attract and retain committed employees, there is the need to put in place appropriate total reward, due to its vital role in enhancing employees' commitment to the organization.…”
Section: Introduction and Background To The Studymentioning
confidence: 99%
“…The reward system is central to the hiring and retention of employees in an organization. Obicci (as cited in Mabaso and Dlamini, 2018) observed that for any employer to be able to attract and retain committed employees, there is the need to put in place appropriate total reward, due to its vital role in enhancing employees' commitment to the organization.…”
Section: Introduction and Background To The Studymentioning
confidence: 99%
“…Reward and performance are symbiotic, and basic pay holds a primary relationship with performance (Abosede & Adekunle, 2012;Ejumudo, 2014;Mabaso & Dlamini, 2018), and salary has a positive relationship with employee performance (Anumudu et al, 2016). Unfortunately, employee performance and motivation are not given proper consideration in policymaking; hence Nigerian universities employees are facing challenges like non-availability of bonuses, overtime, and necessary allowances on the one hand and inadequate training, poor working conditions on the other (Bello, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Basic compensation was second only to work–life balance for tradespeople, and performance‐based bonuses were third (Schlechter et al, ). A South African study of university academics showed basic compensation and fringe benefits correlate positively with organisational commitment (Mabasso & Dlamini, ). According to Mabasso and Dlamini (), “competitive wages and benefits have repeatedly been listed as a means of attracting and retaining employees” (p. 3).…”
Section: Rewards and Incentives To Secure Human Capitalmentioning
confidence: 99%
“…A South African study of university academics showed basic compensation and fringe benefits correlate positively with organisational commitment (Mabasso & Dlamini, ). According to Mabasso and Dlamini (), “competitive wages and benefits have repeatedly been listed as a means of attracting and retaining employees” (p. 3). The importance that workers place on compensation in their jobs challenges health authorities to provide incentives such as pay, benefits and bonuses, to meet their demand for RNs.…”
Section: Rewards and Incentives To Secure Human Capitalmentioning
confidence: 99%